Impact of Tax Planning, Capital Structure, and Corporate Governance on Firm Performance in Indonesia's Real Estate and Construction Sectors - Putri, Anne; Tanno, Aries; Fahlevi, Mochammad (Pusat Penerbitan dan Publikasi Ilmiah, FEB, Universitas Muslim Indonesia, 2022)
Economic growth in Indonesia has consistently increased each year, leading to the COVID-19 pandemic. The pandemic has a considerable impact on the economies of countries worldwide, including Indonesia. Despite the challenging conditions brought about by social restrictions, the company has endeavored to maintain its performance. The pandemic’s negative impact on the national economy was felt across all sectors. The property, real estate, and building construction sectors have experienced a decline in performance. This study investigates the influence of tax planning and capital structure on firm performance, moderated by corporate governance. This research employs multiple regression as the analytical method, using data from 41 real estate, property, and building construction firms listed on the Indonesia Stock Exchange (IDX). The findings reveal that tax planning has a negative impact on firm performance, capital structure has a negative impact on firm performance, and corporate governance has a positive impact on firm performance. Furthermore, our results indicate that corporate governance enhances the negative effects of tax planning on firm performance.